Paradigma Pendidikan Keluarga: Supervisi dan Motiv Keterlibatan Orang Tua dalam Pelaksanaan Ibadah - Muhammad Fahmi Hidayatullah (Tarbiyatuna Kajian Pendidikan Islam, 2018)
Difficult situation of moral degradation whose numbers are increasing every year have sparked the desire of parents to always be involved in the educational process so that this research is important to do. Parental involvement appears in school, community and family life. Family education looks very dominant in involving parents with consideration of family position as basic education in child's life. The key to the success of family education lies in the family process in guiding children to perform worship. In the writing of scientific papers will describe how the obligations and responsibilities of parents to children, and how guidance, encouragement and supervision of parental involvement in the implementation of religious worship. The purpose of this study is to reveal the planning, implementation and supervision in family education. The methodology used is literature research.